Diffusion of propane, propylene and isobutane in 13X zeolite by molecular dynamics - Miguel A. Granato (2010)
This paper presents single component diffusion data of propane, propylene and isobutane in zeolite 13X obtained by molecular dynamics (MD) simulations, especially its dependence on temperature and concentration. Our results are critically compared to experiments and previous simulation data, when available. One novelty of this work is that the diffusion coefficients are computed taking the framework cations of zeolite 13X into consideration. Furthermore, to our knowledge, we present the first simulation results for propylene diffusion in faujasite frameworks. From the mean squared displacements, self-diffusion coefficients of 7.5×109, 9.1×109, and 9.6×1010 m2 s1 for 2 molecules/unit cell were calculated for propane, propylene, and isobutane at 373 K, respectively. The simulations show that the diffusivity decreases with increasing loadings for all adsorbates studied. Finally, transport diffusivities were estimated from the self-diffusion coefficient and the equilibrium adsorption isotherms by using the Darken equation.